Find the differential equation of:
$y = {e^x}\left( {A\cos x + B\sin x} \right)$
Answer
Verified
472.8k+ views
Hint: To obtain the required differential equation of the given equation we will eliminate ‘A’ and ‘B’ from it by taking its first and second order derivatives and solving them together to get the required solution.
Product rule of derivatives$\dfrac{d}{{dx}}\left( {u.v} \right) = u.\dfrac{d}{{dx}}\left( v \right) + v.\dfrac{d}{{dx}}\left( u \right)$, $\dfrac{d}{{dx}}(\sin x) = \cos x,\,\,\,\dfrac{d}{{dx}}\left( {\cos x} \right) = - \sin x$
Complete step-by-step answer:
To find the differential equation of a given function $y = {e^x}\left( {A\cos x + B\sin x} \right)$we have to remove ‘A’ and ‘B’ from it by taking derivatives.
As, there are two variables present in the given equation. So, we differentiate it two times, first we differentiate it to calculate first order derivative $\dfrac{{dy}}{{dx}}$ and then using result we calculate second order derivative$\dfrac{{{d^2}y}}{{d{x^2}}}$.
$y = {e^x}\left( {A\cos x + B\sin x} \right)$
Differentiating w.r.t. ‘x’ we have
$\dfrac{{dy}}{{dx}} = \dfrac{d}{{dx}}\left\{ {{e^x}\left( {A\cos x + B\sin x} \right)} \right\}$
Applying product rule of derivative on right hand side
$\dfrac{{dy}}{{dx}} = {e^x}\dfrac{d}{{dx}}\left( {A\cos x + B\sin x} \right) + \left( {A\cos x + B\sin x} \right)\dfrac{d}{{dx}}\left( {{e^x}} \right)$
$ \Rightarrow \dfrac{{dy}}{{dx}} = {e^x}\left\{ {A\left( { - \sin x} \right) + B\left( {\cos x} \right)} \right\} + \left( {A\cos x + B\sin x} \right){e^x}$
Taking common and simplify above equation
$\dfrac{{dy}}{{dx}} = {e^x}\left\{ { - A\sin x + B\cos x + A\cos x + B\sin x} \right\}$
Or we can write above equation as
$\dfrac{{dy}}{{dx}} = {e^x}\left( { - A\sin x + B\cos x} \right) + {e^x}\left( {A\cos x + B\sin x} \right)$
$ \Rightarrow \dfrac{{dy}}{{dx}} = {e^x}\left( { - A\sin x + B\cos x} \right) + y$ $\because y = {e^x}\left( {A\cos x + B\sin x} \right)$
Or we can write above equation as
$\dfrac{{dy}}{{dx}} - y = {e^x}\left( { - A\sin x + B\cos x} \right)$
Again differentiating above equation to find its double derivative w.r.t. ‘x’
$\dfrac{{{d^2}y}}{{d{x^2}}} - \dfrac{{dy}}{{dx}} = {e^x}\dfrac{d}{{dx}}\left( { - A\sin x + B\cos x} \right) + \left( { - A\sin x + B\cos x} \right)\dfrac{d}{{dx}}\left( {{e^x}} \right)$
$ \Rightarrow \dfrac{{{d^2}y}}{{d{x^2}}} - \dfrac{{dy}}{{dx}} = {e^x}\left( { - A\cos x - B\sin x} \right) + \left( { - A\sin x + B\cos x} \right){e^x}$
Taking ${e^x}$ common from right hand side and simplifying it
$\dfrac{{{d^2}y}}{{d{x^2}}} - \dfrac{{dy}}{{dx}} = {e^x}\left( { - A\cos x - B\sin x - A\sin x + B\cos x} \right)$
$ \Rightarrow \dfrac{{{d^2}y}}{{d{x^2}}} - \dfrac{{dy}}{{dx}} = {e^x}\left( { - A\cos x - B\sin x} \right) + {e^x}\left( { - A\sin x + B\cos x} \right)$
Using vale of $\dfrac{{dy}}{{dx}} - y = {e^x}\left( { - A\sin x + B\cos x} \right)$ calculated above in above equation we have
$\dfrac{{{d^2}y}}{{d{x^2}}} - \dfrac{{dy}}{{dx}} = {e^x}\left( { - A\cos x - B\sin x} \right) + \dfrac{{dy}}{{dx}} - y$
$
\Rightarrow \dfrac{{{d^2}y}}{{d{x^2}}} - 2\dfrac{{dy}}{{dx}} + y = - {e^x}\left( {A\cos x + B\sin x} \right) \\
\Rightarrow \dfrac{{{d^2}y}}{{d{x^2}}} - 2\dfrac{{dy}}{{dx}} + y = - y \\
\Rightarrow \dfrac{{{d^2}y}}{{d{x^2}}} - 2\dfrac{{dy}}{{dx}} + 2y = 0 \\
$
Above equations don’t contain ‘A’ and ‘B’.
So, we can say that this is the required differential equation of the given equations $y = {e^x}\left( {A\cos x + B\sin x} \right)$
Note: To find the differential equation of any given equation we are just required to eliminate the constant present in the given equation. If there is only one constant then we differentiate the given equation only one time to get the required solution but in case if there are two constants then we have to differentiate it up to a double derivative to find the corresponding differential equation.
Product rule of derivatives$\dfrac{d}{{dx}}\left( {u.v} \right) = u.\dfrac{d}{{dx}}\left( v \right) + v.\dfrac{d}{{dx}}\left( u \right)$, $\dfrac{d}{{dx}}(\sin x) = \cos x,\,\,\,\dfrac{d}{{dx}}\left( {\cos x} \right) = - \sin x$
Complete step-by-step answer:
To find the differential equation of a given function $y = {e^x}\left( {A\cos x + B\sin x} \right)$we have to remove ‘A’ and ‘B’ from it by taking derivatives.
As, there are two variables present in the given equation. So, we differentiate it two times, first we differentiate it to calculate first order derivative $\dfrac{{dy}}{{dx}}$ and then using result we calculate second order derivative$\dfrac{{{d^2}y}}{{d{x^2}}}$.
$y = {e^x}\left( {A\cos x + B\sin x} \right)$
Differentiating w.r.t. ‘x’ we have
$\dfrac{{dy}}{{dx}} = \dfrac{d}{{dx}}\left\{ {{e^x}\left( {A\cos x + B\sin x} \right)} \right\}$
Applying product rule of derivative on right hand side
$\dfrac{{dy}}{{dx}} = {e^x}\dfrac{d}{{dx}}\left( {A\cos x + B\sin x} \right) + \left( {A\cos x + B\sin x} \right)\dfrac{d}{{dx}}\left( {{e^x}} \right)$
$ \Rightarrow \dfrac{{dy}}{{dx}} = {e^x}\left\{ {A\left( { - \sin x} \right) + B\left( {\cos x} \right)} \right\} + \left( {A\cos x + B\sin x} \right){e^x}$
Taking common and simplify above equation
$\dfrac{{dy}}{{dx}} = {e^x}\left\{ { - A\sin x + B\cos x + A\cos x + B\sin x} \right\}$
Or we can write above equation as
$\dfrac{{dy}}{{dx}} = {e^x}\left( { - A\sin x + B\cos x} \right) + {e^x}\left( {A\cos x + B\sin x} \right)$
$ \Rightarrow \dfrac{{dy}}{{dx}} = {e^x}\left( { - A\sin x + B\cos x} \right) + y$ $\because y = {e^x}\left( {A\cos x + B\sin x} \right)$
Or we can write above equation as
$\dfrac{{dy}}{{dx}} - y = {e^x}\left( { - A\sin x + B\cos x} \right)$
Again differentiating above equation to find its double derivative w.r.t. ‘x’
$\dfrac{{{d^2}y}}{{d{x^2}}} - \dfrac{{dy}}{{dx}} = {e^x}\dfrac{d}{{dx}}\left( { - A\sin x + B\cos x} \right) + \left( { - A\sin x + B\cos x} \right)\dfrac{d}{{dx}}\left( {{e^x}} \right)$
$ \Rightarrow \dfrac{{{d^2}y}}{{d{x^2}}} - \dfrac{{dy}}{{dx}} = {e^x}\left( { - A\cos x - B\sin x} \right) + \left( { - A\sin x + B\cos x} \right){e^x}$
Taking ${e^x}$ common from right hand side and simplifying it
$\dfrac{{{d^2}y}}{{d{x^2}}} - \dfrac{{dy}}{{dx}} = {e^x}\left( { - A\cos x - B\sin x - A\sin x + B\cos x} \right)$
$ \Rightarrow \dfrac{{{d^2}y}}{{d{x^2}}} - \dfrac{{dy}}{{dx}} = {e^x}\left( { - A\cos x - B\sin x} \right) + {e^x}\left( { - A\sin x + B\cos x} \right)$
Using vale of $\dfrac{{dy}}{{dx}} - y = {e^x}\left( { - A\sin x + B\cos x} \right)$ calculated above in above equation we have
$\dfrac{{{d^2}y}}{{d{x^2}}} - \dfrac{{dy}}{{dx}} = {e^x}\left( { - A\cos x - B\sin x} \right) + \dfrac{{dy}}{{dx}} - y$
$
\Rightarrow \dfrac{{{d^2}y}}{{d{x^2}}} - 2\dfrac{{dy}}{{dx}} + y = - {e^x}\left( {A\cos x + B\sin x} \right) \\
\Rightarrow \dfrac{{{d^2}y}}{{d{x^2}}} - 2\dfrac{{dy}}{{dx}} + y = - y \\
\Rightarrow \dfrac{{{d^2}y}}{{d{x^2}}} - 2\dfrac{{dy}}{{dx}} + 2y = 0 \\
$
Above equations don’t contain ‘A’ and ‘B’.
So, we can say that this is the required differential equation of the given equations $y = {e^x}\left( {A\cos x + B\sin x} \right)$
Note: To find the differential equation of any given equation we are just required to eliminate the constant present in the given equation. If there is only one constant then we differentiate the given equation only one time to get the required solution but in case if there are two constants then we have to differentiate it up to a double derivative to find the corresponding differential equation.
Recently Updated Pages
Master Class 12 Economics: Engaging Questions & Answers for Success
Master Class 12 Maths: Engaging Questions & Answers for Success
Master Class 12 Biology: Engaging Questions & Answers for Success
Master Class 12 Physics: Engaging Questions & Answers for Success
Master Class 12 Business Studies: Engaging Questions & Answers for Success
Master Class 12 English: Engaging Questions & Answers for Success
Trending doubts
Which are the Top 10 Largest Countries of the World?
Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE
Draw a labelled sketch of the human eye class 12 physics CBSE
What is the Full Form of PVC, PET, HDPE, LDPE, PP and PS ?
What is a transformer Explain the principle construction class 12 physics CBSE
What are the major means of transport Explain each class 12 social science CBSE